PENGARUH PEMBERIAN KOMPOS TANDAN KOSONG TANDAN KOSONG KELAPA SAWIT DAN PUPUK PELENGKAP CAIR ORGANIK TERHADAP PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) - Pratama, Acil; ', Adiwirman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The aim of this research was to find out the effect of palm oil empty fruit bunches and complementary organic liquid fertilizer interaction on cocoa’s growth and determine the doses of palm oil empty fruit bunches and complementary liquid fertilizer that giving the highest effect on cocoa seedling’s growth. This research was conducted from October until December 2014 located in the agricultural experimental station, Riau University. The design that used in this research was completely randomized design (CRD) consisted of 2 factors and 3 replications. The first factor waspalm oil empty fruit bunches (K) consisted of 4 levels, were: 0 g (K0), 20 g (K1), 40 g (K2) and 60 g/2 kg soil (K3). The second factor was a complementary organic liquid fertilizer (P) consisted of 4 levels, were: 0 ml (P0), 1 ml (P1), 2 ml (P2) and 3 ml/l water (P3). The result of the research showed that the interaction of palm oil empty fruit bunches and complementary organic liquid fertilizer significantly affected on the cocoa seedling’s growth. Application of 60 g/2 kg soil of palm oil empty fruit bunches and 2 ml/l water complementary organic liquid fertilizer, gave the highest result on plant height, leaf number, steam diameter, leaf area, seedling fresh weight, crown fresh weight, root fresh weight, crown dry weight, root dry weight, crown root ratio, and cocoa seedling dry weight. Keyword: palm oil empty fruit bunches compost, complementary organic liquid fertilizer, cocoa